(untitled) (Critical Journal of Social Sciences, 2026)
This study proposes positioning inner-directed experiences as creative products within Vietnam’s cultural and tourism industry. Inner-directed experiences are understood as tourism activities that encourage tourists to cultivate mindfulness, foster inner connection, and enhance both hedonic and eudaimonic well-being. Drawing on the theoretical foundations of the experience economy and creative tourism, the paper analyzes the potential of cultural, religious, and artistic resources, including Buddhism, Catholicism, Caodaism, Mother Goddess worship, heritage architecture, performing arts, tea rituals, meditation, yoga, and mindful gastronomy. The study introduces a creative value chain model for inner-directed experiences, emphasizing the involvement of local communities, artisans, religious organizations, tourism enterprises, and digital technologies. Elements such as co-creation, virtual and augmented reality, and digital storytelling are highlighted as essential tools for enhancing authenticity, accessibility, and experiential depth. Policy implications are proposed for governments, communities, enterprises, and educational institutions to develop inner-directed experiences as a high-quality and sustainable product segment, with the potential to be scaled up and exported internationally.